2006
DOI: 10.1055/s-2005-921744
|View full text |Cite
|
Sign up to set email alerts
|

‘In situ’ Generated ‘HCl’ - An Efficient Catalyst for Solvent-Free Hantzsch Reaction at Room Temperature: Synthesis of New Dihydropyridine Glycoconjugates

Abstract: HCl, generated in situ from 2,4,6-trichloro[1,3,5]triazine (TCT, cyanuric chloride), catalyzed a solvent free Hantzsch reaction at room temperature with enhanced reaction rates. The reaction conditions allow facile preparation of glycoconjugates of dihydropyridines under mild reaction conditions in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…The Hantzsch reaction involving the sugar-derived aldehydes 84 , ethyl acetoacetate and ammonium acetate was applied by Sharma et al in the synthesis of nucleoside analogs 85 , bearing the 1,4-DHP nucleobase at the C-4- or C-1 carbon atom of the sugar (Scheme 33) [107]. Analogously to the previously reported Biginelli reaction [103], compounds 85 were obtained in high yields under the TCT-catalysis conditions.…”
Section: Reviewmentioning
confidence: 97%
“…The Hantzsch reaction involving the sugar-derived aldehydes 84 , ethyl acetoacetate and ammonium acetate was applied by Sharma et al in the synthesis of nucleoside analogs 85 , bearing the 1,4-DHP nucleobase at the C-4- or C-1 carbon atom of the sugar (Scheme 33) [107]. Analogously to the previously reported Biginelli reaction [103], compounds 85 were obtained in high yields under the TCT-catalysis conditions.…”
Section: Reviewmentioning
confidence: 97%
“…We demonstrated that the ammonium salt could be replaced with ammonia [15]. A number of improved methods have been reported in the literature for this condensation which involve the use of microwave, ionic liquids, reflux high temperature, AlCl 3 ⋅6H 2 O [16], ultrasound irradiation [17], tetrabutylammonium hydrogen sulfate [18], cyanuric chloride [19], molecular iodine [20], silica gelsupported sodium bisulfate [21], TMSCl-NaI [22], scandium(III) triflate [23], CAN [24], iron(III) trifluoroacetate and trifluoromethanesulfonate [25], organocatalysed [26], silica gel/sulfonic acid [27], PTSSA [28], montmorillonite K10 clay [29], and phenylboronic acid [30]. Additionally, dihydropyridines are often produced in a synthetic sequence and have to be oxidized to pyridines [31].…”
Section: Introductionmentioning
confidence: 97%
“…Many synthetic methods for the Electronic supplementary material The online version of this article (doi:10.1007/s10847-015-0540-9) contains supplementary material, which is available to authorized users. synthesis of 1,4-dihydropyridines [28][29][30][31][32][33][34] and pyrimidine [35][36][37][38] derivatives have been reported but into the best of our knowledge there is no report for the synthesis of functionalized-calix [4]arene derivatives with 1,4-dihydropyridine or pyrimidine compound.…”
Section: Introductionmentioning
confidence: 99%